Quality Analysis of Motor Vehicle Tax Service - Rafa Ahdiya Nasyita; Muhamad YGG. Seran; Euis Salbiah (Indonesian Journal of Social Research (IJSR), 2019)
The purpose of this study is to find out how the quality of motor vehicle tax services in the Samsat Office in Bogor City, the theory used in this study is the theory of Zeithaml, Parasuraman & Berry in Hardiansyah (2011), in which there were five dimensions : tangible, reliability, responsiveness, assurance and emphaty. The method used is descriptive analysis method using a quantitative approach. Data analysis techniques use WMS (Weight Mean Score). While the technique of data collection is done using field studies (observation, interviews, questionnaires, and documentation); and literature study. The sample in this study were empleyees and taxpayers of the Samsat Office of Bogor City, totaling 100 (one hundred) people in the population and using accidental sampling techniques. Based on the result of study obtained an average service quality from five dimensions 3,80 which is included in the criteria well. This means that most of the service quality at the Samsat Office Bogor City is good for carrying out its main tasks and functions so that it can help achieve the objectives of the relevant departments. But in reality there are still deficiencies in infrastructure and services that make the service process less than optimal.